2018
DOI: 10.1098/rsta.2017.0137
|View full text |Cite
|
Sign up to set email alerts
|

Tunable, synchronized frequency down-conversion in magnetic lattices with defects

Abstract: We study frequency conversion in nonlinear mechanical lattices, focusing on a chain of magnets as a model system. We show that, by inserting mass defects at suitable locations, we can introduce localized vibrational modes that nonlinearly couple to extended lattice modes. The nonlinear interaction introduces an energy transfer from the high-frequency localized modes to a low-frequency extended mode. This system is capable of autonomously converting energy between highly tunable input and output frequencies, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Moreover, the use of magnetic interactions allows exciting applications. They have already been used as a passive mechanism to couple nodes of a lattice for unidirectional wave-guiding [38]; and it has been suggested that magnetic interactions can be used to design novel devices for frequency conversion [39] and shock absorption [36]. In our study, we focus on breathers in a magnetic chain and demonstrate that there is a crossover from exponential decay to algebraic decay in the spatial profile of these breathers.…”
Section: Introductionmentioning
confidence: 82%
“…Moreover, the use of magnetic interactions allows exciting applications. They have already been used as a passive mechanism to couple nodes of a lattice for unidirectional wave-guiding [38]; and it has been suggested that magnetic interactions can be used to design novel devices for frequency conversion [39] and shock absorption [36]. In our study, we focus on breathers in a magnetic chain and demonstrate that there is a crossover from exponential decay to algebraic decay in the spatial profile of these breathers.…”
Section: Introductionmentioning
confidence: 82%
“…3a). This type of low-order nonlinear interaction is very common in nature, arising in optomechanical systems [24], magnet lattices [25] and vibrating strings [26] among others.…”
Section: B Nor Gate Design and Principle Of Operationmentioning
confidence: 99%
“…Mechanical metamaterials are artificially constructed and have mechanical properties defined by their structure [1]. Simple metamaterials consist of a one, two, or three-dimensional array of elements connected by links [1][2][3] that may be elastic [4][5][6][7], magnetic [8,9] or electrostatic [4]. Mechanical metamaterials are highly tuneable [10][11][12] and by altering the structure of these elements, and the properties of the links, materials have been developed that selectively transmit signals [13,14], behave as logic gates [5,15] or buckle after the application of external stimulus [2].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical metamaterials are artificially constructed and have mechanical properties defined by their structure [1]. Simple metamaterials consist of a one-, two-or three-dimensional array of elements connected by links [1][2][3] that may be elastic [4][5][6][7], magnetic [8,9] or electrostatic [4]. Mechanical metamaterials are highly tuneable [10][11][12] and by altering the 2019 The Author(s) Published by the Royal Society.…”
Section: Introductionmentioning
confidence: 99%